An in situ phosphorization strategy towards doped Co2P scaffolded within echinus-like carbon for overall water splitting. Issue 37 (15th September 2020) - Li, Hui; Xu, Si-Min; Li, Yaru; Yan, Hong; Xu, Sailong
Abstract : An in situ phosphorization route of host/guest precursors is demonstrated to prepare (M0.2 Co0.8 )2 P@C (M = Fe and Ni) electrocatalysts for overall water splitting. EELS observations and DFT calculations underlie the electrocatalytic performances. Abstract : Eco-environmental synthesis of non-expensive electrocatalysts such as transition-metal phosphides (TMPs) is critical to advancing renewable hydrogen fuel. TMP nanostructures prepared typically by introducing additional conventional phosphorus sources are suggested as promising durable and low-cost electrocatalysts. Herein, an eco-efficient guest/host precursor-based synthesis route is demonstrated to prepare doped Co2 P scaffolded within echinus-like carbon ((M0.2 Co0.8 )2 P@C, M = Fe and Ni) as electrocatalysts for overall water splitting. (Fe0.2 Co0.8 )2 P@C is derived by directly pyrolyzing a precursor of sodium dodecyl phosphate-intercalated CoFe-layered double hydroxide (CoFe-LDH), without introducing any additional phosphorus source. Electrocatalytic testing shows that (Fe0.2 Co0.8 )2 P@C requires overpotentials of 290 and 130 mV at a current density of 10 mA cm −2 for oxygen and hydrogen evolution reactions (OER and HER) in an alkaline electrolyte, respectively. Furthermore, a different (Ni0.2 Co0.8 )2 P@C composite, obtained only by altering a NiCo-LDH host, exhibits better electrocatalytic activities than those of Fe-doped (Fe0.2 Co0.8 )2 P@C. In particular, the (No0.2 Co0.8 )2 P@C||(Ni0.2 Co0.8 )2 P@C electrolyzer affords a current density of 10 mA cm −2 at a decent voltage of 1.62 V for overall water splitting. Electron energy-loss spectroscopy (EELS) observations show the oxyhydroxide layer formed on the surface, and density functional theory (DFT) calculations reveal that Fe-/Ni-doping lowers the Gibbs free energy barrier for the OER and the HER, both underpinning the enhancements.